Novel approach to an early assessment of a patient’s potential for neurological remission after acute spinal cord injury: Analysis of hemoglobin concentration dynamics - Biglari, Bahram; Heller, Raban; Hörner, Manuel; Sperl, André; Bock, Tobias; Reible, Bruno; Haubruck, Patrick; Grützner, Paul Alfred; Moghaddam-Alvandi, Arash (The journal of spinal cord medicine, 2021)
Context/objective: Examining hemoglobin (Hb) dynamics with regard to the potential of neurological remission in patients with traumatic spinal cord injury (TSCI).Design: Prospective Clinical Observational Study.Setting: BG Trauma Centre Ludwigshafen, Department of Paraplegiology, Rhineland-Palatinate, Germany.Methods: From 2011 to 2017 a total of 80 patients with acute spinal injury were enrolled and divided into three groups: initial neurological impairment either with (G1; n = 33) or without subsequent neurological remission (G0; n = 35) and vertebral fractures without initial neurological impairment as control group (C; n = 12). Blood samples were taken for 3 months at 11 time-points after injury. Analyses were performed using routine diagnostics.Outcome measures: Multiple logistic regression was used to determine the prognostic value of Hb regarding neurological remission respecting clinical covariates.Results: Data showed elevated mean Hb concentrations in G1 from the third day to 1 month compared to G0, Hb levels were significantly higher in G1 after 3 days (P = 0.03, G1 > G0). The final multiple logistic regression model based on this data predicting the presence of neurological remission resulted in an AUC (area under the curve) of 80.5% (CI: 67.8%-93.2%) in the ROC (receiver operating characteristic) analysis.Conclusion: Elevated Hb concentrations are associated with a higher likelihood of neurological remission. Elevated concentrations of Hb in G1 compared to G0 over time might be linked to both a better initial oxygen supply response and a decreased ECM (extracellular matrix) degradation highlighting the role of Hb as a valuable biomarker for neural regeneration after TSCI.
Online veröffentlicht: 18. Juni 2019
Gesehen am 07.04.2020